Contribution of externally bonded FRP shear reinforcement to the shear strength of RC beams. (1st May 2019) - Oller, Eva; Pujol, Mireia; Marí, Antonio
Abstract: An experimental program of T-beams strengthened in shear by CFRP sheets has been developed with two longitudinal reinforcement ratios and different externally bonded CFRP shear strengthening amounts in a discontinuous or continuous U-shaped configuration with and without mechanical anchorages. The effectiveness of the external reinforcement without anchorages was low regardless the CFRP reinforcement ratio. There is an evidence of the interaction of the different shear strength components, concrete V c, transverse steel V s, CFRP sheets V f that have been obtained from the registered data of the instrumentation. This interaction might explain that the ultimate shear force of some CFRP-strengthened beams was lower than the one of the control beam. There is a significant difference between the sum of the V c, V s, and V f components and the total shear force. This difference is assumed to be carried out by the flange (including its internal transverse reinforcement), which represents a significant percentage of the total shear strength (with a mean value of 38%). Finally, the contribution of the CFRP has been obtained by different existing guidelines and has been compared to the experimental values.